USING MOBILE PHONE TO DETECT THE USER’S INDIVIDUAL RESPONSE TO SPACE WEATHER VARIATIONS - А.А. Abdrakhmanova (European Scientific Journal, ESJ, 2014)
It is shown that there are apparent correlation between cellular networks users' communication activity and the geomagnetic field variations. It is shown that the determination of the appropriate correlation coefficients allows one to define the individual characteristics of users’ reactions to space weather variations. This reaction is characterized by a wide dispersion (as there are meteo-dependent people, there are also people keenly reacting to geomagnetic field variations). It is shown that the identification of individual reactions of the specified type can make the content of the new SMS-services